Guidance and Counseling Strategies to Overcome Students English Speaking Problems at SMA DDI Babussalam Boddie - Rukaya, Rukaya (Jurnal Edukasi Saintifik, 2024)
This study explores the guidance and counseling strategies applied to overcome anxiety of speaking English among high school students of DDI Babussalam Boddie. Anxiety about speaking English can hinder a student's ability to communicate effectively and impact their academic performance. The research method used is a qualitative approach with case study techniques and in-depth interviews. Data were collected through direct observation of guidance and counseling sessions, as well as interviews with students, counselors, and teachers. Data analysis is carried out with a thematic approach to identify the main patterns and themes in the applied strategy. The findings suggest that interventions such as relaxation techniques, speaking skills training, and emotional support are highly effective in improving students' confidence and communication skills.